Dokumentace brzdných stop pomocí fotoaparátu - Kopecký, Štěpán (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2018)
Diplomová práce se zabývá měřením a vyhodnocením brzdných stop u vozidel vybavených systémem ABS. Výsledek práce by měl přispět ke zlepšení kvality pořizování fotodokumentace brzdných stop a k vytvoření postupu, který by co nejvíce eliminoval ztrátu informací během dokumentace stop.

The diploma thesis describes the measurement and evaluation of braking traces in cars equipped by system ABS. The result of the work should contribute to improving the quality of photodocumentation of braking traces. To creating a procedure to eliminate as much as possible the loss of information during tracking documentation.
Documentation of Braking Traces Using a Camera
Keywords: Brzdné stopy; fotodokumentace; systém ABS; úprava fotografii; fotoaparát; Braking traces; photodocumentation; system ABS; editing photos; camera